A delayed remap technique in multi-material ALE methods - Alia, Ahlem; Aquelet, Nicolas; Souli, Mhamed; Olovsson, Lars (European Journal of Computational Mechanics, 2006)
A new mesh refinement method for multi-material ALE formulations is presented. The computational timestep of this approach is divided in 2 steps: a so-called Lagrangian step, during which the mesh deforms with the update of the solution, and a so-called Eulerian step, during which the mesh is remapped in order to preserve the mesh regularity and refine in the vicinity of the shock front. As test case the method is applied to the propagation of an explosive airblast, for which experimental results are available.